Comparative study of use of prophylactic antibiotic for elective hernia repair with use of prosthetic material: observational study in a tertiary care institute - Umman, Philip; Jose, Joyal; Ahmed, Althaf; Xavier, Jeenu (International Surgery Journal, 2017)
Background: There is widespread misuse of antibiotics leading to increasing reports of drug resistance. This has been highlighted by the World Health Organization (WHO). Wrong antibiotics are chosen, used when not indicated and used in dosages or patterns that are not recommended. We tried to analyse the pattern of antibiotic use for elective hernia repair using polypropylene mesh among the surgical units in our hospital for elective clean cases. The antibiotic use pattern and the incidence of surgical site infections were to be analysed to create uniform policies for antibiotic use across the institution. Methods: We looked at the case records of patients undergoing elective hernia repair in one month in our institution under different surgeons. Inguinal, umbilical and simple incisional hernias were taken into study. Both open and laparoscopic hernia repairs were included in the study. Emergency hernia repairs were excluded. We looked at the type of prophylactic antibiotic given, the dose and approximate time difference between injection and incision time, whether patient received further doses of intravenous or oral antibiotic. If further doses were given, we also looked for reasons if documented. These cases were followed for one month to see if there was any difference in the incidence of surgical site infections. Results: There were thirty-one cases, of which 16 received only a single dose of prophylactic antibiotic while 15 received more than one dose of antibiotic. Only one patient in the prophylactic antibiotic only group developed a culture positive wound infection. There was seroma formation in two patients. Conclusions: There was no evidence of higher incidence of wound infection in patients receiving only prophylactic antibiotic. There is a need for developing institution specific policies on antibiotic use. This will reduce the treatment costs and also avoid the development of antibiotic resistance in the society.